Effect of The Covid-19 Pandemic on Teaching In Subject of Anatomy For First MBBS Students: Effect of The Covid-19 Pandemic on Teaching In Subject of Anatomy (GAIMS Journal of Medical Sciences, 2022)
Introduction: Anatomical knowledge is very crucial to the practice of medicine; thus, its acquisition is foundation base for clinicalsubjects. Many studies have shown that cadaveric dissections strengthen respect and empathy among medical students. Manystudents felt the stress and anxiety due to online teaching classes during the pandemicMaterial and methods: This cross-sectional study was conducted among first year MBBS students of Gujarat Adani Institute ofMedical Sciences, Bhuj, Gujarat, India, during 2020-2021. Informed consent was taken from the students when they came back tooffline classes after the pandemic was controlledResults: Students were of opinion that offline teaching is more stimulating, it is easy to engage with teacher and more interactionand doubt can be cleared. But during online teaching fear of facing teacher was less in minds of students.The disadvantages which are associated with online teaching as per our study were mostly poor internet connection and lessinteractivity with teacher. Regarding advantages of online teaching, students were most happy with flexibility of location andcomfort of home. Other few advantages were time and cost saving due to travel.Conclusion: The present study revealed that for anatomy being a vast subject, online teaching cannot replace the offline teaching.But in current corona pandemic, online teaching is the only way out. To make online teaching effective it should be more interactiveand practical topic has to be revised on specimens and models when students are back to offline classes. The exams should not justinclude MCQs but also viva and assignments